Neuropathy of haematopoietic stem cell niche is essential for myeloproliferative neoplasms - Arranz, Lorena; Sánchez-Aguilera, Abel; Martín-Pérez, Daniel; Isern, Joan; Langa, Xavier; Tzankov, Alexandar; Lundberg, Pontus; Muntión, Sandra; Tzeng, Yi-Shiuan; Lai, Dar-Ming; Schwaller, Jürg; Skoda, Radek C.; et al. (Nature (London), 2014)
Myeloproliferative neoplasms are caused by mutations in the haematopoietic stem cell (HSC) compartment, and here the authors show that the HSC niche contributes to the pathogenesis; sympathetic innervation of mesenchymal stem cells (MSCs) is reduced in the bone marrow of patients, which leads to reduced MSC numbers and increased mutant HSC expansion, and restoring sympathetic regulation of MSCs with neuroprotective/sympathomimetic drugs prevents mutant HSC expansion. Pathogenesis of myeloproliferative neoplasms The stem cell niche has recently been recognized as an oncogenic unit and an important element in regulating cancer stem cells. Here, Simón Méndez-Ferrer and colleagues demonstrate that sympathetic innervation of nestin-positive mesenchymal stem cells (MSCs) in the bone marrow microenvironment is reduced in patients with myeloproliferative neoplasms. This denervation leads to reduced MSC numbers and increased mutant haematopoietic stem cell (HSC) expansion. When sympathetic regulation of nestin-positive MSCs is restored by neuroprotective drugs, mutant HSC expansion is prevented. Myeloproliferative neoplasms (MPNs) are diseases caused by mutations in the haematopoietic stem cell (HSC) compartment. Most MPN patients have a common acquired mutation of Janus kinase 2 ( JAK2 ) gene in HSCs 1 , 2 , 3 , 4 that renders this kinase constitutively active, leading to uncontrolled cell expansion. The bone marrow microenvironment might contribute to the clinical outcomes of this common event. We previously showed that bone marrow nestin + mesenchymal stem cells (MSCs) innervated by sympathetic nerve fibres regulate normal HSCs 5 , 6 . Here we demonstrate that abrogation of this regulatory circuit is essential for MPN pathogenesis. Sympathetic nerve fibres, supporting Schwann cells and nestin + MSCs are consistently reduced in the bone marrow of MPN patients and mice expressing the human JAK2(V617F) mutation in HSCs. Unexpectedly, MSC reduction is not due to differentiation but is caused by bone marrow neural damage and Schwann cell death triggered by interleukin-1β produced by mutant HSCs. In turn, in vivo depletion of nestin + cells or their production of CXCL12 expanded mutant HSC number and accelerated MPN progression. In contrast, administration of neuroprotective or sympathomimetic drugs prevented mutant HSC expansion. Treatment with β 3 -adrenergic agonists that restored the sympathetic regulation of nestin + MSCs 5 , 6 prevented the loss of these cells and blocked MPN progression by indirectly reducing the number of leukaemic stem cells. Our results demonstrate that mutant-HSC-driven niche damage critically contributes to disease manifestation in MPN and identify niche-forming MSCs and their neural regulation as promising therapeutic targets.